Increasing Marketing and Production Capacity Through Bamboo Handicraft Managerial Training in Kayubihi Village, Bangli.: Peningkatan Kapasitas Pemasaran dan Produksi melalui Pelatihan Manajerial pada Pengrajin Bambu Desa Kayubihi, Bangli - Ni Made Wahyuni; I Wayan Gede Suacana; Kadek Goldina Puteri Dewi; Dian Pramana (Universitas Lancang Kuning, 2025)
Kayubihi Village is located in Bangli Regency which has natural resources of bamboo trees and creative talent. This opportunity creates a bamboo handicraft business that supports the village economy. However, the analysis of the situation found a problem, namely that the artisan group was unable to meet the needs of business-to-business orders. Taking into account these issues, this activity establishes two main steps: procurement of equipment facilities as an investment in production, and training activities, so that production and marketing capacity and turnover increase. KKN-PMM partners are a group of Bamboo Masterpiece craftsmen. The goal of the program is to improve the quality of human resources in the aspects of production, marketing, and finance. The flow of activities taken in the training is with socialization, counseling, training, and mentoring. The participatory method of environmental scanning, which is participatory from the target community, is used in this service activity. The results of the training show an increase in the ability to use innovative technological equipment, the ability to make product designs according to business needs or desires, the ability to create financial ledgers, and the ability to use social media platforms to market bamboo products.